Participation and occupation in occupational therapy models of practice: A discussion of possibilities and challenges. (2nd November 2017) - Larsson-Lund, Maria; Nyman, Anneli
Abstract: Background: Occupation has been the focus in occupational therapy practice to greater or lesser degrees from a historical viewpoint. This evokes a need to discuss whether concepts that are added to our field will enhance or blur our focus on occupation. Aim: To explore how the concept of participation in the International Classification of Functioning, Disability and Health (ICF) is related to the concept of occupation by reviewing and comparing its use in three models of practice within occupational therapy. The aim was also to generate discussion on possibilities and challenges concerning the relationship of participation and occupation. Method: The models reviewed were The Model of Human Occupation (MOHO), the Canadian Model of Occupational Performance and Engagement (CMOP-E) and the Occupational Therapy Intervention Process Model (OTIPM). Results: The concept of participation was related to occupation in different ways in these models. Based on the review some challenges and considerations for occupational therapy were generated. Conclusion: Relating the concept of participation from the ICF to the concept of occupation in models of practice can be challenging. At the same time, relating the concepts can be a resource to develop occupational therapy and the understanding of occupational issues in society.